Pengaruh Penggunaan Media Whatsapp selama Masa Pandemi Covid-19 terhadap Pembelajaran PPKN (Penelitian di SMA YAS Sindangkerta KabupatenBandung Barat) - Ernandia Pandikar; Edy Sofyan; Yayang Suryani (Neolectura, 2022)
In the Covid-19 pandemic situation, learning at school was hampered, and one of them was PPKN lessons. The alternative used by PPKN teachers at YAS Sindangkerta High School in learning is to use WhatsApp media. The purpose of conducting this research was to determine the effect of using WhatsApp media during the Covid-19 pandemic on PPKN lessons at SMA YAS Sindangkerta. The research method used is descriptive quantitative research using a survey method, as well as collecting data using a questionnaire. The sample in this study amounted to 33 students with the entire population, namely class XII, totaling 217 students. The results of the study were seen from the t Hypothesis Test which showed that the significance value of using WhatsApp media in the coefficient table was 0.001, less than 0.05. This means that the use of WhatsApp media during the Covid-19 pandemic had an effect on being used in Civics learning. The result of the Correlation Coefficient test is the Pearson Correlation value of 0.543, which means that the correlation level between the two variables is moderate.